Potential of waqf instrument in tourism industry in Malaysia / Norajila Che Man...[et.al] - Che Man, Norajila; Abd Wahab, Nor Azlina; Ab Hamid, Norafifah; Nordin, Rawi (Center for Islamic Philantrophy & Social Finance (CIPSF), 2019)
Waqf is one of the essential instruments in developing the economy of the Muslims. The role of waqf is not only limited to intrinsic worship but it also covers all areas of development such as education, health, economic activities, agriculture and so on. Waqf can also play its role in developing the tourism industry which is one of the activities recommended in Islam as tourism is a platform to develop the society in terms of culture, heritage, society and economy. In Malaysia, the tourism industry acts as one of the main sectors contributing to the country’s economic growth. The practice of waqf in tourism in Malaysia can be viewed through the efforts made by JAWHAR and other agencies due to the awareness of ensuring waqf properties are developed through a contemporary approach. This paper focuses on the role of waqf in Islamic-based tourism sector in Malaysia.